A polyurethane composite material for high-speed rail and its preparation method and application

The polyurethane composite material for high-speed rail is made of a specific ratio of raw materials, which solves the problems of low strength, poor insulation and insufficient flame retardant performance of existing high-speed rail vibration-absorbing devices, and achieves efficient vibration-absorbing effect and good corrosion resistance. .

CN118685023BActive Publication Date: 2025-02-11JIANGXI LONGZHENG TECH DEV CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410842920.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-27
Publication Date
2025-02-11
Estimated Expiration
2044-06-27

AI Technical Summary

Technical Problem

Existing high-speed rail vibration-absorbing device materials such as steel and aluminum alloys have high weight, low strength, poor insulation and corrosion resistance, and polymer materials have shortcomings in impact resistance, fatigue resistance and flame retardant properties.

Method used

Use specific ratios of preparation materials to make polyurethane composite materials for high-iron, including flame retardant polyether polyols, isocyanates, modified nano zinc oxide, catalysts, mixed fibers and specific amide compounds, and improve the material through blending and crosslinking technology. Mechanical properties, flame retardant properties and corrosion resistance.

Benefits of technology

It improves the mechanical properties, flame retardant properties and corrosion resistance of polyurethane composite materials, enhances vibration damping effect, reduces noise generation, and extends the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004914886740000141
    Figure BDA0004914886740000141
Patent Text Reader

Abstract

The present application relates to the technical field of polyurethane, specifically a polyurethane composite material for high-speed rail and its preparation method and application, including raw materials: 8-12 parts of flame-retardant polyether polyol, 6-8 parts of isocyanate, 1-2 parts of modified nano zinc oxide, 0.02-0.04 parts of catalyst, 5-10 parts of mixed fiber, 4,4'-methylenebis(2-chloroaniline) 4-6 parts, N,N-methylenebisacrylamide 2-3 parts; mixed fiber includes aramid fiber and basalt fiber; the preparation method of flame-retardant polyether polyol includes: taking isophorone diisocyanate, adding dibutyltin dilaurate, heating, dropping polyethylene glycol monomethyl ether, vacuum distillation, and obtaining an intermediate product; taking bisphenol A type epoxy resin and heating, under a protective gas atmosphere, dropping phenylphosphonic acid, adding benzyl triethylamine chloride and the intermediate product, vacuum distillation, and obtaining flame-retardant polyether polyol. The polyurethane composite material prepared by matching specific raw materials has good corrosion resistance and flame retardancy while improving the mechanical properties of polymer materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polyurethane, and in particular to a polyurethane composite material for high-speed rail and a preparation method and application thereof. Background Art

[0002] With the rapid development of my country's high-speed railways, the operating mileage of high-speed railways has been increasing. High-speed railways have the advantages of high speed, large capacity, energy saving and comfort, and are the best choice to solve urban traffic problems. However, the operation of high-speed railways has brought many environmental problems along the railways, especially vibration and noise, which seriously affect the normal life of passengers and people along the tracks. On the other hand, noise and vibration may also cause fatigue of the locomotive equipment and surrounding buildings, shortening their service life.

[0003] In order to reduce the impact of vibration, a vibration reduction device is usually installed at the bottom of the locomotive. The existing vibration reduction device is made of steel and aluminum alloy, which is not only heavy and low in strength, but also has poor insulation and corrosion resistance.

[0004] The use of polymer materials can improve the elasticity and insulation properties of vibration reduction devices. For example, replacing alloys with rubber materials can increase the elasticity of the material and thus improve the vibration reduction effect. However, rubber materials have high viscosity, poor oil resistance, and difficult process operation. At the same time, the product's impact resistance and fatigue resistance cannot be met. In addition, polymer materials also pose a fire hazard due to their poor flame retardancy. Summary of the invention

[0005] The present application aims to overcome at least one of the defects of the prior art and provide a polyurethane composite material for high-speed rail and a preparation method and application thereof. The polyurethane composite material prepared by selecting specific raw materials for combination has good corrosion resistance and flame retardancy while improving the mechanical properties of general polymer materials.

[0006] In the first aspect, the embodiment of the present application provides a polyurethane composite material for high-speed rail, which is achieved by the following technical solutions:

[0007] A polyurethane composite material for high-speed rail, comprising the following raw materials in parts by weight:

[0008] 8-12 parts of flame retardant polyether polyol, 6-8 parts of isocyanate, 1-2 parts of modified nano zinc oxide, 0.02-0.04 parts of catalyst, 5-10 parts of mixed fiber, 4-6 parts of 4,4'-methylenebis(2-chloroaniline), 2-3 parts of N,N-methylenebisacrylamide;

[0009] Wherein, the mixed fiber includes aramid fiber and basalt fiber;

[0010] The preparation method of the flame retardant polyether polyol is:

[0011] S1. Take isophorone diisocyanate (IPDI for short), add dibutyltin dilaurate, heat to 30-40 ° C, gradually add polyethylene glycol monomethyl ether dropwise within 25-35 minutes, determine the -NCO content by di-n-butylamine titration, react until NCO% is stable, and distill under reduced pressure at a temperature of 90-105 ° C to obtain an intermediate product;

[0012] S2. Take bisphenol A epoxy resin and heat it to 85-95 ° C. Under a protective gas atmosphere, phenylphosphonic acid is gradually added dropwise within 18-25min. After the addition is completed, react for 2-3 hours, add benzyl triethylamine chloride and the intermediate product, react until NCO% <0.1%, and distill under reduced pressure at 90-105 ° C to obtain a flame retardant polyether polyol;

[0013] The molar ratio of the polyethylene glycol monomethyl ether to the isophorone diisocyanate in step S1 is 1:(1-1.3);

[0014] The molar ratio of the bisphenol A epoxy resin to the phenylphosphonic acid in step S2 is (4-5):2.

[0015] A polyurethane composite material for high-speed rail according to an embodiment of the present application has at least the following beneficial effects:

[0016] The polyurethane composite material of the present application is matched by selecting different components. The aramid fiber in the mixed fiber has good mechanical properties, excellent flame retardancy, heat resistance and stable chemical properties. The basalt fiber in the mixed fiber has good corrosion resistance, high temperature resistance and thermal shock stability, high elastic modulus and tensile strength. The polyurethane is blended with the mixed fiber so that the mixed fiber can be effectively filled into the gaps in the polyurethane material. At the same time, N,N-methylenebisacrylamide is added for cross-linking to improve the strength and stability of the polyurethane material.

[0017] This application introduces phosphorus and nitrogen elements by modifying polyether polyols. Nitrogen and phosphorus synergistically improve the flame retardant properties of polyurethane composites. At the same time, multiple benzene rings are introduced to further enhance its flame retardancy and corrosion resistance and improve the toughness of the material. When dibutyltin dilaurate is used as a catalyst, the activity of the two -NCO groups in the IPDI molecule is very different. The -NCO directly connected to the cyclohexane is less affected by the substituent and steric hindrance, and its activity is more than 10 times higher than that of the other -NCO group. Therefore, polyethylene glycol monomethyl ether is added dropwise to IPDI, and IPDI is always in excess, so that the highly active -NCO reacts first, and an intermediate product containing monoisocyanate can be obtained.

[0018] The molar ratio of bisphenol A epoxy resin to phenylphosphonic acid is greater than 2:1, and phenylphosphonic acid containing terminal epoxy groups is obtained. The terminal epoxy groups react with -NCO of the intermediate product to introduce hydrophilic polyethylene glycol segments into the molecule. Since phenylphosphonic acid has two active hydrogens, it can react with two bisphenol A epoxy resins and be capped by two epoxy groups. Therefore, two polyethylene glycol segments can be introduced into one polyether polyol molecule, which has better hydrophilicity and can effectively reduce the length of the hydrophilic segment in the molecule. At the same time, this branched structure can reduce the hydrodynamic volume of the molecule, improve fluidity, and improve the elasticity of the prepared polyurethane material.

[0019] According to some embodiments of the present application, the molar number of dibutyltin dilaurate in step S1 is 0.8-1.2% of the molar number of polyethylene glycol monomethyl ether.

[0020] According to some embodiments of the present application, the protective gas in step S2 is selected from one of nitrogen, helium, neon, and argon, for example, the protective gas is nitrogen. Nitrogen is widely available and has low production costs. It can form an oxygen-free environment to prevent epoxy groups, isocyanates, etc. from being oxidized and destroyed, and reduce the occurrence of side reactions. Rare gases such as helium, neon, and argon are stable in nature and are not easily involved in chemical reactions, which can reduce the generation of side reactions.

[0021] According to some embodiments of the present application, the molar ratio of the intermediate product to the phenylphosphonic acid in step S2 is (1.9-2.1):1; the molar ratio of the intermediate product to the phenylphosphonic acid containing a terminal epoxy group is controlled to be around 2:1 to facilitate the full reaction and improve the utilization rate of the raw materials.

[0022] According to some embodiments of the present application, the molar number of benzyltriethylammonium chloride in step S2 is 2-4% of the molar number of phenylphosphonic acid.

[0023] According to some embodiments of the present application, the preparation method of the modified nano zinc oxide is:

[0024] A1. Ultrasonic dispersion of nano zinc oxide in a mixed solution of anhydrous ethanol and deionized water (8-9):1 mass ratio, and adding coupling agent KH-550 under stirring, raising the temperature to 70-80 ° C, constant temperature magnetic stirring for 5-8h, centrifugation, washing, drying to obtain organosilicon-modified nano zinc oxide;

[0025] A2. Graphene pretreatment: Graphene is ultrasonically dispersed in a mixed solution of sulfuric acid and nitric acid, then refluxed at 80°C for 4 hours, and dried and ground after the reaction is completed;

[0026] A3. Add the graphene pretreated in step A2 to ethanol for ultrasonic dispersion, add the organosilicon-modified nano zinc oxide prepared in step A1, stir rapidly at 25-35°C to allow it to react fully, centrifuge, wash several times with anhydrous ethanol, dry in vacuum, and grind to obtain modified nano zinc oxide.

[0027] Modified nano zinc oxide is used as a filler in polyurethane composites. Nano materials can enhance the mechanical properties of polyurethane due to their large specific surface area and high adsorption performance; zinc oxide can effectively improve the antioxidant and corrosion resistance; silicone can increase the dispersion of nano zinc oxide in the polyurethane matrix, improve the elasticity, wear resistance, corrosion resistance and flame retardancy of polyurethane composites; after acidification, the surface of graphene will be oxidized into carboxyl groups, which will combine with silicone-modified nano zinc oxide, reducing the problem of easy agglomeration of graphene. The layered structure of graphene makes the mixing between filler and resin more complete, thereby improving the high temperature resistance and tensile strength of polyurethane composites.

[0028] Furthermore, the mass ratio of the nano zinc oxide, the anhydrous ethanol and the coupling agent KH-550 is 1:(8-10):(0.1-0.2).

[0029] According to some embodiments of the present application, the mass ratio of the aramid fiber to the basalt fiber is (2-3):(1-2).

[0030] According to some embodiments of the present application, the diameter of the hybrid fiber is 10 μm-1000 μm.

[0031] According to some embodiments of the present application, the length of the mixed fiber is 0.5 cm-2 cm.

[0032] Blending small diameter and short length fibers can more effectively fill the voids in the polyurethane material, further improving the strength and stability of the polyurethane material.

[0033] According to some embodiments of the present application, the isocyanate includes at least one of toluene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, and tetramethylxylylene diisocyanate.

[0034] According to some embodiments of the present application, the catalyst includes at least one of organic tin and organic bismuth.

[0035] Furthermore, the catalyst includes at least one of dibutyltin diacetate, stannous octoate, dibutyltin dilaurate, and bismuth laurate.

[0036] In a second aspect, the present application provides a method for preparing the above-mentioned polyurethane composite material for high-speed rail, which is achieved by the following technical solutions:

[0037] A method for preparing a polyurethane composite material for high-speed rail comprises the following steps:

[0038] The flame retardant polyether polyol is dehydrated at a temperature of 100-120°C and a vacuum degree of -0.1MPa for 1-2h; the temperature is lowered to 60-80°C, the isocyanate is added, and the prepolymer is reacted at 78-82°C for 1.5-2h to synthesize the prepolymer; the prepolymer is vacuum degassed at a temperature of 78-82°C and a vacuum degree of -0.1MPa for 0.5-1h; the catalyst, the modified nano zinc oxide, the 4,4'-methylenebis(2-chloroaniline), the N,N-methylenebisacrylamide, and the mixed fiber are added, heated to 110-120°C and stirred to mix evenly; at the same time, the mold is preheated to 80-110°C, a release agent is applied to the mold, the mold is poured, the mold is first vulcanized at a temperature of 100-120°C for 0.5-1h, the mold is demoulded, and the second vulcanization is performed at a temperature of 100°C for 16-24h to obtain a polyurethane composite material for high-speed rail.

[0039] According to a method for preparing a polyurethane composite material for high-speed rail according to an embodiment of the present application, there are at least the following beneficial effects:

[0040] The present application adopts a prepolymer method to prepare a polyurethane elastomer, and the reaction is carried out in two steps. Due to the prepolymerization step, the heat release during the chain extension reaction is low and easy to control. The obtained polyurethane molecular chain segments are arranged relatively regularly, the product has good mechanical properties and good repeatability. The preparation method of the present application has simple steps, does not require the use of complex production equipment, has low cost, and is suitable for industrial production.

[0041] The solution of the present application uses two vulcanizations to make the hydrogen bonds and sulfur bonds between the polyurethane chains more fully combined, the formed cross-linked structure more stable, and the connections between the polyurethane molecules more tightly, thereby increasing the strength and hardness of the polyurethane.

[0042] In a third aspect, the embodiments of the present application provide the use of the polyurethane composite material for high-speed rail in the manufacture of a high-speed rail shock absorbing device. The use of the polyurethane composite material of the present application in the high-speed rail shock absorbing device can enhance the vibration reduction effect, reduce the generation of noise, and reduce the impact on passengers and people along the track. DETAILED DESCRIPTION

[0043] To make the purpose, technical solution and advantages of the present application clearer, the following will be further described in detail in conjunction with specific embodiments. The embodiments described here are only part of the embodiments of the present application and cannot be understood as limiting the scope of protection of the present application.

[0044] Preparation Example 1 of Flame Retardant Polyether Polyol

[0045] Preparation of flame retardant polyether polyols:

[0046] S1. Take 6 mol of isophorone diisocyanate, add 0.05 mol of dibutyltin dilaurate, heat to 35 ° C, gradually add 5 mol of polyethylene glycol monomethyl ether dropwise within 30 min, determine the -NCO content by di-n-butylamine titration, react until NCO% is stable, distill at a temperature of 100 ° C and a vacuum of 8 kPa to obtain an intermediate product;

[0047] S2. Take 4.5 mol of bisphenol A epoxy resin and heat it to 90°C. Under a nitrogen protective gas atmosphere, gradually add 2 mol of phenylphosphonic acid within 20 minutes. After the addition is completed, react for 2 hours. Add 0.06 mol of benzyl triethylamine chloride catalyst and 3.9 mol of the intermediate product, react until NCO% is less than 0.1%, and distill at a temperature of 95°C and a vacuum of 8 kPa to obtain a flame retardant polyether polyol.

[0048] Preparation Example 2 of Flame Retardant Polyether Polyol

[0049] Preparation of flame retardant polyether polyols:

[0050] S1. Take 5.5 mol of isophorone diisocyanate, add 0.04 mol of dibutyltin dilaurate, heat to 35 ° C, gradually add 5 mol of polyethylene glycol monomethyl ether dropwise within 30 min, determine the -NCO content by di-n-butylamine titration, react until NCO% is stable, distill at a temperature of 90 ° C and a vacuum of 8 kPa to obtain an intermediate product;

[0051] S2. Take 5 mol of bisphenol A epoxy resin and heat it to 90°C. Under a nitrogen protective gas atmosphere, gradually add 2 mol of phenylphosphonic acid within 20 minutes. After the addition is completed, react for 3 hours. Add 0.04 mol of benzyl triethylamine chloride catalyst and 4 mol of the intermediate product, react until NCO% is less than 0.1%, and distill at a temperature of 105°C and a vacuum of 8 kPa to obtain a flame retardant polyether polyol.

[0052] Preparation Example 3 of Flame Retardant Polyether Polyol

[0053] Preparation of flame retardant polyether polyols:

[0054] S1. Take 6.5 mol of isophorone diisocyanate, add 0.06 mol of dibutyltin dilaurate, heat to 35 ° C, gradually add 5 mol of polyethylene glycol monomethyl ether dropwise within 30 min, determine the -NCO content by di-n-butylamine titration, react until NCO% is stable, distill at a temperature of 105 ° C and a vacuum of 8 kPa to obtain an intermediate product;

[0055] S2. Take 4 mol of bisphenol A epoxy resin and heat it to 90°C. Under a nitrogen protective gas atmosphere, gradually add 2 mol of phenylphosphonic acid within 20 minutes. After the addition is completed, react for 2 hours. Add 0.08 mol of benzyl triethylamine chloride catalyst and 4.1 mol of the intermediate product, react until NCO% is less than 0.1%, and distill at a temperature of 90°C and a vacuum of 8 kPa to obtain a flame retardant polyether polyol.

[0056] Flame retardant polyether polyol comparative example 1

[0057] Preparation of flame retardant polyether polyols:

[0058] Take 4.5 mol of bisphenol A epoxy resin and heat it to 90°C. Under a nitrogen protective gas atmosphere, gradually add 2 mol of phenylphosphonic acid within 20 minutes. After the addition is completed, react for 2 hours. Add 0.06 mol of benzyl triethylamine chloride catalyst and distill at a temperature of 95°C and a vacuum of 8 kPa to obtain a flame retardant polyether polyol.

[0059] Preparation Example 1 of Modified Nano Zinc Oxide

[0060] Preparation of modified nano zinc oxide:

[0061] A1. 10 g of nano zinc oxide was ultrasonically dispersed in 100 g of a mixed solution of anhydrous ethanol and deionized water in a mass ratio of 9:1, and 2 g of coupling agent KH-550 was added under stirring. The temperature was raised to 75°C, and magnetic stirring was performed at a constant temperature for 6 hours. After centrifugation, washing, and drying, organosilicon-modified nano zinc oxide was obtained;

[0062] A2. Graphene pretreatment: Graphene is ultrasonically dispersed in a mixed solution of sulfuric acid and nitric acid, then refluxed at 80°C for 4 hours, and dried and ground after the reaction is completed;

[0063] A3. Add the graphene pretreated in step A2 to ethanol for ultrasonic dispersion, add the organosilicon-modified nano zinc oxide prepared in step A1, stir rapidly at 30°C to allow it to react fully, centrifuge, wash several times with anhydrous ethanol, dry in vacuum, and grind to obtain modified nano zinc oxide.

[0064] Preparation Example 2 of Modified Nano Zinc Oxide

[0065] Preparation of modified nano zinc oxide:

[0066] A1. 10 g of nano zinc oxide was ultrasonically dispersed in 90 g of a mixed solution of anhydrous ethanol and deionized water in a mass ratio of 8:1, and 1 g of coupling agent KH-550 was added under stirring. The temperature was raised to 80°C and magnetically stirred at a constant temperature for 8 h. After centrifugation, washing and drying, organosilicon-modified nano zinc oxide was obtained.

[0067] A2. Graphene pretreatment: Graphene is ultrasonically dispersed in a mixed solution of sulfuric acid and nitric acid, then refluxed at 80°C for 4 hours, and dried and ground after the reaction is completed;

[0068] A3. Add the graphene pretreated in step A2 to ethanol for ultrasonic dispersion, add the organosilicon-modified nano zinc oxide prepared in step A1, stir rapidly at 25°C to allow it to react fully, centrifuge, wash several times with anhydrous ethanol, dry in vacuum, and grind to obtain modified nano zinc oxide.

[0069] Modified Nano Zinc Oxide Comparative Example 1

[0070] Preparation of modified nano zinc oxide:

[0071] 10 g of nano zinc oxide was ultrasonically dispersed in 100 g of a mixed solution of anhydrous ethanol and deionized water in a mass ratio of 9:1, and 2 g of coupling agent KH-550 was added under stirring. The temperature was raised to 75°C and magnetic stirring was performed at a constant temperature for 6 hours. After centrifugation, washing and drying, organosilicon-modified nano zinc oxide was obtained.

[0072] Example 1

[0073] Preparation of polyurethane composite materials for high-speed rail: raw materials are selected by weight: 10 parts of flame-retardant polyether polyol prepared in Preparation Example 1 of flame-retardant polyether polyol, 7 parts of toluene diisocyanate, 1 part of modified nano zinc oxide prepared in Preparation Example 1 of modified nano zinc oxide, 0.03 parts of dibutyltin diacetate, 9 parts of mixed fiber, 5 parts of 4,4'-methylenebis(2-chloroaniline), and 3 parts of N,N-methylenebisacrylamide; wherein the mixed fiber is formed by mixing aramid fiber and basalt fiber in a weight ratio of 2:1; the diameter of the mixed fiber is 10 μm-1000 μm, and the length of the mixed fiber is 0.5 cm-2 cm;

[0074] The flame retardant polyether polyol was dehydrated at a temperature of 110°C and a vacuum degree of -0.1MPa for 1.5h; the temperature was lowered to 70°C, toluene diisocyanate was added, and the prepolymer was reacted at 80°C for 1.8h; the prepolymer was vacuum degassed at a temperature of 80°C and a vacuum degree of -0.1MPa for 0.8h; dibutyltin diacetate, modified nano zinc oxide, 4,4'-methylenebis(2-chloroaniline), N,N-methylenebisacrylamide, and mixed fiber were added, and the mixture was stirred and mixed evenly at 115°C; at the same time, the mold was preheated to 100°C, a release agent was applied to the mold, and the mold was poured. The mold was first vulcanized at a temperature of 110°C for 0.8h, demolded, and secondly vulcanized at a temperature of 100°C for 20h to obtain a polyurethane composite material for high-speed rail.

[0075] Example 2

[0076] Preparation of polyurethane composite materials for high-speed rail: raw materials are selected by weight: 8 parts of flame-retardant polyether polyol prepared in Preparation Example 1 of flame-retardant polyether polyol, 6 parts of hexamethylene diisocyanate, 2 parts of modified nano zinc oxide prepared in Preparation Example 1 of modified nano zinc oxide, 0.02 parts of stannous octoate, 5 parts of mixed fiber, 6 parts of 4,4'-methylenebis(2-chloroaniline), and 2 parts of N,N-methylenebisacrylamide; wherein the mixed fiber is formed by mixing aramid fiber and basalt fiber in a weight ratio of 3:2; the diameter of the mixed fiber is 10 μm-1000 μm, and the length of the mixed fiber is 0.5 cm-2 cm;

[0077] The flame retardant polyether polyol was dehydrated at a temperature of 120°C and a vacuum degree of -0.1MPa for 1h; the temperature was lowered to 80°C, hexamethylene diisocyanate was added, and the prepolymer was reacted at 78°C for 2h; the prepolymer was vacuum degassed at a temperature of 78°C and a vacuum degree of -0.1MPa for 1h; stannous octoate, modified nano zinc oxide, 4,4'-methylenebis(2-chloroaniline), N,N-methylenebisacrylamide, and mixed fiber were added, and the mixture was stirred and mixed evenly at 120°C; at the same time, the mold was preheated to 80°C, a release agent was applied to the mold, and the mold was poured. The mold was first vulcanized at a temperature of 120°C for 0.5h, demolded, and secondly vulcanized at a temperature of 100°C for 24h to obtain a polyurethane composite material for high-speed rail.

[0078] Example 3

[0079] Preparation of polyurethane composite materials for high-speed rail: raw materials are selected by weight: 12 parts of flame-retardant polyether polyol prepared in Preparation Example 1 of flame-retardant polyether polyol, 8 parts of tetramethylxylene diisocyanate, 1 part of modified nano zinc oxide prepared in Preparation Example 1 of modified nano zinc oxide, 0.04 parts of bismuth laurate, 10 parts of mixed fiber, 4 parts of 4,4'-methylenebis(2-chloroaniline), and 3 parts of N,N-methylenebisacrylamide; wherein the mixed fiber is formed by mixing aramid fiber and basalt fiber in a weight ratio of 3:1; the diameter of the mixed fiber is 10 μm-1000 μm, and the length of the mixed fiber is 0.5 cm-2 cm;

[0080] The flame retardant polyether polyol was dehydrated at a temperature of 100°C and a vacuum degree of -0.1MPa for 2h; the temperature was lowered to 60°C, tetramethylxylene diisocyanate was added, and the prepolymer was reacted at 82°C for 1.5h; the prepolymer was vacuum degassed at a temperature of 82°C and a vacuum degree of -0.1MPa for 0.5h; bismuth laurate, modified nano zinc oxide, 4,4'-methylenebis(2-chloroaniline), N,N-methylenebisacrylamide, and mixed fiber were added, and the mixture was stirred and evenly mixed at 110°C; at the same time, the mold was preheated to 110°C, a release agent was applied to the mold, and the mold was poured. The mold was first vulcanized at a temperature of 100°C for 1h, demolded, and secondly vulcanized at a temperature of 100°C for 16h to obtain a polyurethane composite material for high-speed rail.

[0081] Comparative Example 1

[0082] Preparation of polyurethane composite material: Select raw materials by weight: 10 parts of flame retardant polyether polyol prepared in Preparation Example 1 of flame retardant polyether polyol, 7 parts of toluene diisocyanate, 1 part of modified nano zinc oxide prepared in Preparation Example 1 of modified nano zinc oxide, 0.03 parts of dibutyltin diacetate, and 5 parts of 4,4'-methylenebis(2-chloroaniline);

[0083] The flame retardant polyether polyol was dehydrated at a temperature of 110°C and a vacuum degree of -0.1MPa for 1.5h; the temperature was lowered to 70°C, toluene diisocyanate was added, and the prepolymer was reacted at 80°C for 1.8h; the prepolymer was vacuum degassed at a temperature of 80°C and a vacuum degree of -0.1MPa for 0.8h; dibutyltin diacetate, modified nano zinc oxide, and 4,4'-methylenebis(2-chloroaniline) were added, and the mixture was stirred and mixed uniformly at 115°C; at the same time, the mold was preheated to 100°C, a release agent was applied to the mold, and the mold was poured. The mold was first vulcanized at a temperature of 110°C for 0.8h, demolded, and secondly vulcanized at a temperature of 100°C for 20h to obtain a polyurethane composite material.

[0084] Comparative Example 2

[0085] Preparation of polyurethane composite materials:

[0086] Preparation of polyurethane composite materials: Select raw materials by weight: 10 parts of flame retardant polyether polyol prepared in flame retardant polyether polyol comparative example 1, 7 parts of toluene diisocyanate, 1 part of modified nano zinc oxide prepared in modified nano zinc oxide preparation example 1, 0.03 parts of dibutyltin diacetate, 9 parts of mixed fiber, 5 parts of 4,4'-methylenebis(2-chloroaniline), and 3 parts of N,N-methylenebisacrylamide; wherein the mixed fiber is formed by mixing aramid fiber and basalt fiber in a weight ratio of 2:1; the diameter of the mixed fiber is 10 μm-1000 μm, and the length of the mixed fiber is 0.5 cm-2 cm;

[0087] The flame retardant polyether polyol was dehydrated at a temperature of 110°C and a vacuum degree of -0.1MPa for 1.5h; the temperature was lowered to 70°C, toluene diisocyanate was added, and the prepolymer was reacted at 80°C for 1.8h to synthesize the prepolymer; the prepolymer was vacuum degassed at a temperature of 80°C and a vacuum degree of -0.1MPa for 0.8h; dibutyltin diacetate, modified nano zinc oxide, 4,4'-methylenebis(2-chloroaniline), N,N-methylenebisacrylamide, and mixed fiber were added, and the mixture was stirred and mixed evenly at 115°C; at the same time, the mold was preheated to 100°C, a release agent was applied to the mold, and the mold was poured. The mold was first vulcanized at a temperature of 110°C for 0.8h, demolded, and secondly vulcanized at a temperature of 100°C for 20h to obtain a polyurethane composite material.

[0088] Comparative Example 3

[0089] Preparation of polyurethane composite materials: Select raw materials by weight: 10 parts of flame-retardant polyether polyol prepared in Preparation Example 1 of flame-retardant polyether polyol, 7 parts of toluene diisocyanate, 1 part of modified nano zinc oxide prepared in Comparative Example 1 of modified nano zinc oxide, 0.03 parts of dibutyltin diacetate, 9 parts of mixed fiber, 5 parts of 4,4'-methylenebis(2-chloroaniline), and 3 parts of N,N-methylenebisacrylamide; wherein the mixed fiber is formed by mixing aramid fiber and basalt fiber in a weight ratio of 2:1;

[0090] The flame retardant polyether polyol was dehydrated at a temperature of 110°C and a vacuum degree of -0.1MPa for 1.5h; the temperature was lowered to 70°C, toluene diisocyanate was added, and the prepolymer was reacted at 80°C for 1.8h; the prepolymer was vacuum degassed at a temperature of 80°C and a vacuum degree of -0.1MPa for 0.8h; dibutyltin diacetate, modified nano zinc oxide, 4,4'-methylenebis(2-chloroaniline), N,N-methylenebisacrylamide, and mixed fiber were added, and the mixture was stirred and mixed evenly at 115°C; at the same time, the mold was preheated to 100°C, a release agent was applied to the mold, and the mold was poured. The mold was first vulcanized at a temperature of 110°C for 0.8h, demolded, and secondly vulcanized at a temperature of 100°C for 20h to obtain a polyurethane composite material for high-speed rail.

[0091] Comparative Example 4

[0092] Preparation of polyurethane composite materials: Select raw materials by weight: 10 parts of flame retardant polyether polyol prepared in Preparation Example 1 of flame retardant polyether polyol, 7 parts of toluene diisocyanate, 1 part of nano zinc oxide, 0.03 parts of dibutyltin diacetate, 9 parts of mixed fiber, 5 parts of 4,4'-methylenebis(2-chloroaniline), and 3 parts of N,N-methylenebisacrylamide; wherein the mixed fiber is formed by mixing aramid fiber and basalt fiber in a weight ratio of 2:1; the diameter of the mixed fiber is 10 μm-1000 μm, and the length of the mixed fiber is 0.5 cm-2 cm;

[0093] The flame retardant polyether polyol is dehydrated at a temperature of 110°C and a vacuum degree of -0.1MPa for 1.5h; the temperature is lowered to 70°C, toluene diisocyanate is added, and the prepolymer is reacted at 80°C for 1.8h to synthesize the prepolymer; the prepolymer is vacuum degassed at a temperature of 80°C and a vacuum degree of -0.1MPa for 0.8h; dibutyltin diacetate, nano zinc oxide, 4,4'-methylenebis(2-chloroaniline), N,N-methylenebisacrylamide, and mixed fiber are added, and the mixture is stirred and evenly mixed at 115°C; at the same time, the mold is preheated to 100°C, a release agent is applied to the mold, and the mold is poured. The mold is first vulcanized at a temperature of 110°C for 0.8h, demolded, and secondly vulcanized at a temperature of 100°C for 20h to obtain a polyurethane composite material.

[0094] Experimental example

[0095] The polyurethane composite materials prepared in Examples 1-3 and Comparative Examples 1-3 were taken, their appearances were observed, and the tensile strength, flame retardancy, and corrosion resistance were tested. The testing methods were as follows:

[0096] The flexural strength and flexural modulus are tested according to the standard of GB / T 9341-2008.

[0097] The tensile strength is tested according to the standard of GB / T 1040-92.

[0098] The flame retardant grade is tested according to the standard of GB 8624-2012.

[0099] The corrosion resistance is tested according to the standard of GB / T 3857-2017. If the surface gloss, color, obvious softening or hardening, cracks, delamination, fiber exposure, swelling and other appearance of the sample remain unchanged, the corrosion resistance is recorded as level 1 (corrosion resistant); if at least one of the surface gloss, color, obvious softening or hardening, cracks, delamination, fiber exposure, swelling and other appearance of the sample changes slightly, the corrosion resistance is recorded as level 2 (still corrosion resistant); if at least one of the surface gloss, color, obvious softening or hardening, cracks, delamination, fiber exposure, swelling and other appearance of the sample changes significantly, the corrosion resistance is recorded as level 3 (not corrosion resistant).

[0100] The test data is shown in Table 1 below:

[0101] Table 1

[0102]

[0103] It can be seen from Table 1 that the polyurethane composite materials for high-speed rail prepared in Examples 1-3 of the present application have a smooth appearance, no cracks, no delamination, excellent mechanical properties such as bending strength, bending modulus, and tensile strength, and have good corrosion resistance and flame retardancy.

[0104] The preparation raw materials of Comparative Example 1 do not contain mixed fibers. The mechanical properties of the polyurethane composite material prepared in Comparative Example 1, such as bending strength, bending modulus, and tensile strength, are significantly inferior to those of Example 1 of the present application. At the same time, the corrosion resistance and flame retardancy are also affected. This indicates that adding a specific ratio of mixed fibers to the preparation raw materials in the present application is very important for improving the comprehensive performance of the polyurethane composite material.

[0105] The flame retardant polyether polyol prepared in Example 1 is used as the raw material for the preparation of Comparative Example 2. No nitrogen element is introduced into the flame retardant polyether polyol, and the rest is the same as Example 1. The polyurethane composite material prepared in Comparative Example 2 has poor flame retardancy and corrosion resistance, which indicates that in the preparation method of the flame retardant polyether polyol of the present application, phosphorus and nitrogen elements are introduced, and nitrogen and phosphorus synergistically can improve the flame retardant properties of the polyurethane composite material. At the same time, the introduction of multiple benzene rings can further enhance its flame retardancy and corrosion resistance and improve the toughness of the material.

[0106] The modified nano zinc oxide prepared in Comparative Example 1 is used as the raw material for the preparation of Comparative Example 3, and has not been modified with graphene. The rest is the same as Example 1. The appearance of the polyurethane composite material prepared in Comparative Example 3 shows slight stratification, and its corrosion resistance and mechanical properties are not as good as those in Example 1, indicating that graphene modification can make the nano zinc oxide filler mixed with polyurethane more fully, thereby improving the performance of the polyurethane composite material.

[0107] Ordinary nano zinc oxide is used in the preparation raw materials of Comparative Example 4, and the rest are the same as Example 1. The polyurethane composite material prepared in Comparative Example 4 has slight voids in appearance, and its corrosion resistance is significantly deteriorated. Its flame retardancy and mechanical properties are also inferior to those of Example 1, indicating that silicone modification can improve the dispersion of nano zinc oxide, reduce particle agglomeration, and prevent the generation of voids. At the same time, silicone can further improve the flame retardancy and corrosion resistance of the polyurethane composite material.

[0108] Although the embodiments of the present application have been shown and described, those skilled in the art will appreciate that various changes, modifications, substitutions or variations may be made to the embodiments without departing from the principles and purpose of the present application, and that the technical solutions after these changes, modifications, substitutions or variations will fall within the scope of protection of the present application.

Claims

1. A polyurethane composite material for high-speed rail, characterized in that: The preparation comprises the following raw materials in parts by weight: 8-12 parts of flame retardant polyether polyol, 6-8 parts of isocyanate, 1-2 parts of modified nano zinc oxide, 0.02-0.04 parts of catalyst, 5-10 parts of mixed fiber, 4-6 parts of 4,4'-methylenebis(2-chloroaniline), 2-3 parts of N,N-methylenebisacrylamide; Wherein, the mixed fiber includes aramid fiber and basalt fiber; The preparation method of the flame retardant polyether polyol comprises: S1. Take isophorone diisocyanate, add dibutyltin dilaurate, heat to 30-40 ° C, gradually add polyethylene glycol monomethyl ether dropwise within 25-35min, determine the -NCO content by di-n-butylamine titration, react until NCO% is stable, and distill under reduced pressure at a temperature of 90-105 ° C to obtain an intermediate product; S2. Take bisphenol A epoxy resin and heat it to 85-95 ° C. Under a protective gas atmosphere, phenylphosphonic acid is gradually added dropwise within 18-25min. After the addition is completed, react for 2-3 hours, add benzyl triethylamine chloride and the intermediate product, react until NCO% <0.1%, and distill under reduced pressure at 90-105 ° C to obtain a flame retardant polyether polyol; The molar ratio of the polyethylene glycol monomethyl ether to the isophorone diisocyanate in step S1 is 1:(1-1.3); The molar ratio of the bisphenol A epoxy resin to the phenylphosphonic acid in step S2 is (4-5):

2.

2. The polyurethane composite material for high-speed rail according to claim 1, characterized in that: The weight ratio of the aramid fiber to the basalt fiber is (2-3):(1-2).

3. The polyurethane composite material for high-speed rail according to claim 1, characterized in that: The diameter of the mixed fiber is 10 μm-1000 μm, and / or the length of the mixed fiber is 0.5 cm-2 cm.

4. The polyurethane composite material for high-speed rail according to claim 1, characterized in that: The molar ratio of the intermediate product to the phenylphosphonic acid is (1.9-2.1):

1.

5. The polyurethane composite material for high-speed rail according to claim 1, characterized in that: The molar number of the dibutyltin dilaurate in step S1 is 0.8-1.2% of the molar number of the polyethylene glycol monomethyl ether, and / or the molar number of the benzyltriethylammonium chloride in step S2 is 2-4% of the molar number of the phenylphosphonic acid.

6. The polyurethane composite material for high-speed rail according to claim 1, characterized in that: The preparation method of the modified nano zinc oxide comprises: A1. Ultrasonic dispersion of nano zinc oxide in a mixed solution of anhydrous ethanol and deionized water (8-9):1 mass ratio, and adding coupling agent KH-550 under stirring, raising the temperature to 70-80 ° C, constant temperature magnetic stirring for 5-8h, centrifugation, washing, drying to obtain organosilicon-modified nano zinc oxide; A2. Graphene pretreatment: Graphene is ultrasonically dispersed in a mixed solution of sulfuric acid and nitric acid, then refluxed at 80°C for 4 hours, and dried and ground after the reaction is completed; A3. Add the graphene pretreated in step A2 to ethanol for ultrasonic dispersion, add the organosilicon-modified nano zinc oxide prepared in step A1, stir rapidly at 25-35°C to allow it to react fully, centrifuge, wash several times with anhydrous ethanol, dry in vacuum, and grind to obtain modified nano zinc oxide.

7. The polyurethane composite material for high-speed rail according to claim 6, characterized in that: The mass ratio of the nano zinc oxide, the anhydrous ethanol and the coupling agent KH-550 in step A1 is 1:(8-10):(0.1-0.2).

8. The polyurethane composite material for high-speed rail according to claim 1, characterized in that: The isocyanate includes at least one of toluene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, and tetramethylxylylene diisocyanate, and / or the catalyst includes at least one of organic tin and organic bismuth.

9. A method for preparing the polyurethane composite material for high-speed railway according to any one of claims 1 to 8, characterized in that: The following steps are involved: The flame retardant polyether polyol is dehydrated at a temperature of 100-120°C and a vacuum degree of -0.1MPa for 1-2h; the temperature is lowered to 60-80°C, the isocyanate is added, and the prepolymer is reacted at 78-82°C for 1.5-2h to synthesize the prepolymer; the prepolymer is vacuum degassed at a temperature of 78-82°C and a vacuum degree of -0.1MPa for 0.5-1h; the catalyst, the modified nano zinc oxide, the 4,4'-methylenebis(2-chloroaniline), the N,N-methylenebisacrylamide, and the mixed fiber are added, heated to 110-120°C and stirred to mix evenly; at the same time, the mold is preheated to 80-110°C, a release agent is applied to the mold, the mold is poured, the mold is first vulcanized at a temperature of 100-120°C for 0.5-1h, the mold is demoulded, and the second vulcanization is performed at a temperature of 100°C for 16-24h to obtain a polyurethane composite material for high-speed rail.

10. Use of the polyurethane composite material for high-speed rail as claimed in any one of claims 1 to 8 in the manufacture of high-speed rail shock absorbing devices.

Citation Information

Patent Citations

  • Polyurethane damping cushion with high cold resistance and preparation method thereof

    CN107602817A

  • Environment-friendly anti-seismic foam and preparation method thereof

    CN114672153A